The Influence of Collaborative Learning on Students' Writing Skills in Descriptive Text of The Eleventh Grade - Simanungkalit, Hotnola; Damanik, Bernike Anggita; Purba, Rudiarman (CV Putra Publisher, 2026)
Writing skills are one of the important skills in learning English, especially in writing descriptive texts. However, students often have difficulty developing ideas, using the right vocabulary, and constructing sentences in accordance with the structure of descriptive texts. To overcome this problem, this research examines the influence of collaborative learning on the descriptive writing skills of XI grade students at SMA Negeri 2 Pematangsiantar. This research used a quantitative approach with a quasi-experimental design. The research subjects involved 61 students from two sample classes, namely XI-7 (30 students) as the experimental class and XI-10 (31 students) as the control class, using purposive sampling. The experimental group was taught using Collaborative Learning, while the control group was taught using conventional methods. Data were collected through pre-test and post-test written tests, then analyzed using an independent sample t-test. The results showed that the average pre-test scores for the experimental and control classes were 55.67 and 51.26, respectively, while the post-test scores increased to 82.13 and 71.19. Thus, the experimental class experienced an increase of 26.46, while the control class only increased by 19.93. This comparison shows that the increase in the experimental class score was higher than that of the control class. The t-test produced a significance value of 0.000 < 0.05, which means that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. This indicates that there is a significant difference between students taught using collaborative learning and students taught using conventional methods. Based on the research findings, it can be concluded that the use of collaborative learning significantly improves students' writing skills in descriptive texts